Optimization of electrospinning parameters for polyacrylonitrile-MgO nanofibers applied in air filtration. (1st September 2016) - Dehghan, Somayeh Farhang; Golbabaei, Farideh; Maddah, Bozorgmehr; Latifi, Masoud; Pezeshk, Hamid; Hasanzadeh, Mahdi; Akbar-Khanzadeh, Farhang
ABSTRACT: The present study aimed to optimize the electrospinning parameters for polyacrylonitrile (PAN) nanofibers containing MgO nanoparticle to obtain the appropriate fiber diameter and mat porosity to be applied in air filtration. Optimization of applied voltage, solution concentration, and spinning distance was performed using response surface methodology. In total, 15 trials were done according to the prepared study design. Fiber diameter and porosity were measured using scanning electron microscopic (SEM) image analysis. For air filtration testing, the nanofiber mat was produced based on the suggested optimum conditions for electrospinning. According to the results, the lower solution concentration favored the thinner fiber. The larger diameter gave a higher porosity. At a given spinning distance, there was a negative correlation between fiber diameter and applied voltage. Moreover, there were curvilinear relationships between porosity and both spinning distance and applied voltage at any concentration. It was also concluded that the developed filter medium could be comparable to the high-efficiency particulate air (HEPA) filter in terms of collection efficiency and pressure drop. The empirical models presented in this study can provide an orientation to the subsequent experiments to form uniform and continuous nanoﬁbers for future application in air purification. Implications : High-efficiency filtration is becoming more important, due to decreasing trends air quality. Effective filter media are increasingly needed in industries applying clean-air technologies, and the necessity for developing the high-performance air filters has been more and more felt. Nanofibrous filter media that are mostly fabricated via electrospinning technique have attracted considerable attention in the last decade. The present study aimed to develop the electrospun PAN-containing MgO nanoparticle (using the special functionalities such as absorption and adsorption characteristics, antibacterial functionality, and as a pore-forming agent) filter medium through experimental investigations for application in high-performance air filters.